2023
DOI: 10.1111/jcmm.17671
|View full text |Cite
|
Sign up to set email alerts
|

CLEFMA induces intrinsic and extrinsic apoptotic pathways through ERK1/2 and p38 signalling in uterine cervical cancer cells

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…ERK1/2 are downstream components of the phosphorylation cascade of MAPK, which is closely related to biological functions including cell proliferation, differentiation, migration and invasion (50,51). Although ERK1/2 protein often acts as a survival promoting factor in the MAPK family (52,53), an increasing number of studies have demonstrated that activation of the ERK1/2 protein can induce cell apoptosis (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…ERK1/2 are downstream components of the phosphorylation cascade of MAPK, which is closely related to biological functions including cell proliferation, differentiation, migration and invasion (50,51). Although ERK1/2 protein often acts as a survival promoting factor in the MAPK family (52,53), an increasing number of studies have demonstrated that activation of the ERK1/2 protein can induce cell apoptosis (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…The way curcumin analogs boost the efficacy of anti-immune checkpoint inhibitors also represents a new research field under development [ 30 ]. Finally, among the 25 recently reviewed curcumin analogs [ 15 ], at least eight have been the subject of continuous investigations with respect to their pleiotropic anticancer effects, in 2023 alone [ 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 ]. As these molecules may overcome limitations of bioavailability and pharmacokinetics that were recently reviewed based on clinical data [ 17 ], the hope is that the current research might soon lead to clinical trials involving cancer patients for at least some of them.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in papillomavirus (HPV)-positive cervical cancer cells, curcumin suppresses proliferation and migration by directly targeting the viral oncoprotein E6 protein, subsequently activating p53 and p21 [186]. Interestingly, Lee et al [187] discovered that the curcumin derivative, CLEFMA, triggers intrinsic and extrinsic apoptotic pathways by activating ERK1/2 and p38 signaling [187]. Conversely, EF24 suppresses cellular migration and MMP-9 expression by inhibiting p38 signaling [188].…”
Section: Curcuminmentioning
confidence: 99%